Immunogenicity persistence of hepatitis A vaccines Healive® and Havrix® among children:15 years follow-up and long-term prediction - Xiaoli Wang; Wenguo Xu; Yuansheng Hu; Hui Yao; Li Xu; Minhua Ma; Ying Zhang; Yalong Wang (Taylor & Francis Group, 2023)
Healive® was the only Chinese WHO-prequalified inactivated vaccine for the hepatitis A virus, which has been widely used in national immunization programs in China. Long-term follow-up studies are needed to estimate the persistence of vaccine-induced antibody levels and the necessity for booster vaccines. During the trial, geometric mean concentrations (GMCs) and seroconversion rates (SRs) of anti-HAV antibodies were compared based on two different inactivated hepatitis A vaccines, Healive® and Havrix®. Four hundred children were randomly assigned to receive two doses of Healive® or Havrix® at 0 and 6 months. The current study assessed antibody persistence for both vaccines 15 years post-immunization. A mixed linear model was used to predict long-term antibody persistence. The GMCs were significantly higher for Healive® compared to Havrix® at 1, 6, 7, 66, 138 months (P < .001) and 186 months (P = .004 < .05) post-vaccination. Healive® and Havrix® reached a GMC of 164.8 mIU/ml and 105.7 mIU/ml post-15 years of vaccination, respectively. The seroconversion rates of both vaccines showed no statistically significant differences (97.9% for Healive® and 94.7% for Havrix®, P = .20). The prediction showed that Healive® would provide protection for a minimum of 30 years following immunization, with a lower limit of the 95% confidence intervals for GMCs greater than 20mIU/mL. Compared to Havrix®, the vaccine Healive® showed a stronger protective effect and better persistence among children at 15 years post-full immunization. Prediction indicated at least 30 years of antibody persistence for Healive® and at least 25 years for Havrix®.